2011
DOI: 10.2174/187152711799219307
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylethanolamide Restores Myelinated-Fibre Function in Patients with Chemotherapy-Induced Painful Neuropathy

Abstract: We assessed the effect of palmitoylethanolamide (PEA) on pain and nerve function in patients with chemotherapy-induced painful neuropathy, in 20 patients undergoing thalidomide and bortezomib treatment for multiple myeloma. All patients were evaluated before and after a two-month treatment with PEA 300 mg BID using pain and warmth thresholds; blinded examiners measured motor and sensory nerve fibre function and laser-evoked potentials. Although no variables returned to normal values, pain and all neurophysiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 34 publications
1
39
0
Order By: Relevance
“…Consistent with this notion, PEA administration restored nerve function in patients diagnosed with CIPN who were undergoing thalidomide and bortezomib treatment of multiple myeloma. In particular, Truini et al (2011) demonstrated that PEA exerted a positive action on myelinated fibers through the regulation of mast cell hyperactivity, providing significant restoration of nerve function. Thus, PEA may exert a similar effect to prevent paclitaxel-induced peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this notion, PEA administration restored nerve function in patients diagnosed with CIPN who were undergoing thalidomide and bortezomib treatment of multiple myeloma. In particular, Truini et al (2011) demonstrated that PEA exerted a positive action on myelinated fibers through the regulation of mast cell hyperactivity, providing significant restoration of nerve function. Thus, PEA may exert a similar effect to prevent paclitaxel-induced peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted cytoprotection such as protection against neurotoxicity and ototoxicity is much sought after. In 2011 the group of Professor Cruccu of the University of Rome, published the results of a clinical trial in 20 patients, showing that the natural compound Palmitoylethanolanide (PEA) administered concomitantly to thalidomide and bortezomib could reduce neuropathic pain after chemotherapy and restore the disturbed neurophysiology of nerves [1]. These results support the notion of targeted cytoprotection during chemotherapy.…”
mentioning
confidence: 85%
“…Acety-L-Carnitine [65], Alpha-lipoic acid [66], Amifostine [67], cholest-4-en-3-one, oxime (TRO19622) [68], Cannabinoid type-1 receptor [69], Gabapentin [70], Glutamine [71], Lamotrigine [72], recombinant human leukemia inhibitory factor (rhuLIF, AM424, emfilermin) [73], Neurosteroids [74], Palmitoylethanolamide [75] and Retinoic acid [76] were studied individually for their efficacy in randomized clinical trials.…”
Section: Medical Managementmentioning
confidence: 99%